Adab teachers of Islamic religious education in Singapore: Analysis of the guidance book of the Asatizah Recognition Scheme (ARS) - Bin Zulkifli, Musa; Alpizar; Bte Salman, Nola Fibriyani (Tawazun: Jurnal Pendidikan Islam, 2023)
Among the problems faced by Singaporean Muslim educators is the issue of asatizah etiquette. Given their position as teachers, asatizahs become role models for madrasa students and the local Muslim community. For this reason, Islamic religious leaders in Singapore see the need for an accreditation or certification institution for educators or commonly referred to as asatizah in Singapore. The purpose of this article is to see what and how the accreditation institution for asatizahs called the Asatizah Recognition Scheme (ARS), as well as analyzing the manners of asatizahs in Singapore which are the provisions in the Asatizah Recognition Scheme (ARS). This research method uses a qualitative method with a literature research approach. The author obtains data from official documents related to the asatizah certification policy in Singapore issued by the Singapore Islamic Religious Council (MUIS) and the Asatizah Recognition Board (ARB). The results of this study found that the Asatizah Recognition Scheme (ARS) program is a kind of teacher certification intended for all who teach Islamic science in Singapore. The program aims to improve the competence of Islamic religious education teachers so that they can become a credible source of reference for Singapore’s Islamic community. The competence is given only to religious teachers who are worthy and suitable for preaching and teaching religion in Singapore. The teacher’s manners are things that must be obeyed by teachers who take part in the Asatizah Recognition Scheme (ARS) program, called the code of ethics. With this code of ethics, it is hoped that asatizahs will further improve their professionalism so that they can increase the trust of the Islamic community in Singapore towards asatizahs. Abstrak Di antara masalah yang dihadapi oleh para pendidik muslim Singapura adalah masalah adab atau etika asatizah. Mengingat posisinya sebagai guru, asatizah menjadi role mode bagi para siswa madrasah dan masyarakat muslim setempat. Untuk itu, para pemuka agama Islam di Singapura memandang perlu adanya lembaga akreditasi atau sertifikasi bagi pendidik atau biasa disebut dengan asatizah di Singapura. Tujuan artikel ini adalah untuk melihat apa dan bagaimana lembaga akreditasi untuk para asatizah yang dinamakan Asatizah Recognition Scheme (ARS), juga menganalisis adab para asatizah di Singapura yang menjadi ketentuan dalam Asatizah Recognition Scheme (ARS). Metode penelitian ini menggunakan metode kualitatif dengan pendekatan penelitian kepustakaan. Penulis mendapatkan data-data dari dokumen-dokumen resmi yang berkaitan dengan kebijakan sertifikasi asatizah di Singapura yang diterbitkan oleh Majelis Ugama Islam Singapura (MUIS) dan Asatizah Recognition Board (ARB). Hasil penelitian ini mendapati bahwa program Asatizah Recognition Scheme (ARS) menjadi semacam sertifikasi guru yang diperuntukan untuk semua yang mengajar keilmuan Islam di Singapura. Program ini bertujuan untuk meningkatkan kompetensi guru pendidikan agama Islam agar bisa menjadi sumber rujukan yang kredibel bagi masyarakat Islam Singapura. Kompetensi tersebut diberikan hanya kepada guru-guru agama yang layak dan sesuai untuk berdakwah dan mengajar agama di Singapura Adapun adab guru menjadi hal yang harus dipatuhi oleh para guru yang mengikuti program Asatizah Recognition Scheme (ARS), dinamakan sebagai kode etik. Dengan adanya kode etik tersebut, diharapkan para asatizah semakin meningkatkan profesionalismenya sehingga bisa meningkatkan kepercayaan masyarakat Islam di Singapura terhadap para asatizah.